Product Quality and Asymmetric Exchange Rate Pass-Through in the Iron and Steel Industry between Thailand and Vietnam - Termprasertsakul, Santi; Jearviriyaboonya, Jakkrich (Journal of Applied Economics and Management Strategy, 2022)
ABSTRACT This paper studies the impact of product quality on the degree of exchange rate pass-through (ERPT) by investigating 19 products at the HS 4-digit level in the iron and steel industry, mostly traded between Thailand and Vietnam. Vertical product differentiation is applied to measure the heterogeneous quality of iron and steel traded between Thailand and Vietnam. The monthly data for 2010-2019 period are used in the analysis. Furthermore, this study employs a Nonlinear Autoregressive Distributed Lag (NARDL) model to examine the asymmetric behavior of exchange rate pass through with heterogeneous level of product quality. The empirical results reveal a complete pass-through in the long run and an incomplete pass-through in the short run. The product quality affects the degree of ERPT through to import prices. In addition, the asymmetry of ERPT is captured in the long run as well as the short run.